Finitely semi-graded algebras and Koszulity (2018)
The aim of this work is to introduce the class of finitely semi-graded algebras which is a generalization of finitely graded algebras generated in degree one, and include important examples whithin the skew P BW extensions. We study Koszul behavior of finitely semi-graded algebras investigating the distributivity of some associated ideal lattices. Also, we discuss the Hilbert series, the Poincaré series and the Yoneda algebra for this class of algebras.